Pengaruh Pendapatan Orang Tua dan Motivasi Belajar Terhadap Hasil Belajar Mata Pelajaran Ekonomi - Wulandari Wulandari; Armida S; Dessi Susanti (Universitas Negeri Padang, 2022)
This study aims to determine how the influence of parents' income and learning motivation on economic learning outcomes in class XII IPS SMAN 3 Pariaman. This type of research is descriptive associative research using SPSS. The population in this study were all students of class XII IPS totaling 87 students. The data used are primary data and secondary data. The data collection technique is by using a questionnaire. The sampling technique used in this study is total sampling with a total of 87 respondents. The analytical method used is path analysis using SPSS. To test the research hypothesis, it was conducted using data analysis through validity and reliability tests, normality tests, heteroscedasticity, path analysis, F tests and t tests. The results of this study indicate that: (1) There is a positive and significant effect of parents' income on students' learning motivation, (2) There is a positive and significant influence of parents' income on learning outcomes. 3) There is no significant effect of student learning motivation on learning outcomes. (4) Indirectly, parental income has no significant effect on student learning outcomes through learning motivation. Keywords: parents' income, learning motivation, learning outcomes